2011
DOI: 10.1016/j.febslet.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsisactin-depolymerizing factors (ADFs) 1 and 9 display antagonist activities

Abstract: a b s t r a c tWe provide evidence that one of the 11 Arabidopsis actin-depolymerizing factors (ADFs), namely ADF9, does not display typical F-actin depolymerizing activity. Instead, ADF9 effectively stabilizes actin filaments in vitro and concomitantly bundles actin filaments with the highest efficiency under acidic conditions. Competition experiments show that ADF9 antagonizes ADF1 activity by reducing its ability to potentiate F-actin depolymerization. Accordingly, ectopic expression of ADF1 and ADF9 in tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…For example, ADF1, ADF2, ADF4, and ADF7 of Arabidopsis, ADF3 of maize (Zea mays), and ADF1 of lily (Lilium longiflorum) possess these conserved biochemical activities in vitro (Allwood et al, 2002;Maciver and Hussey, 2002;Ren and Xiang, 2007;Zheng et al, 2013), and their activities are typically increased at elevated pH. Interestingly, ADF9 from Arabidopsis showed actin-bundling and actin-stabilizing activities in vitro, especially at lower pH, that were absolutely distinct from the activities of other conserved ADF family proteins (Tholl et al, 2011). In addition, it has been noted that the activities of ADFs from various organs or plant species may differ slightly.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ADF1, ADF2, ADF4, and ADF7 of Arabidopsis, ADF3 of maize (Zea mays), and ADF1 of lily (Lilium longiflorum) possess these conserved biochemical activities in vitro (Allwood et al, 2002;Maciver and Hussey, 2002;Ren and Xiang, 2007;Zheng et al, 2013), and their activities are typically increased at elevated pH. Interestingly, ADF9 from Arabidopsis showed actin-bundling and actin-stabilizing activities in vitro, especially at lower pH, that were absolutely distinct from the activities of other conserved ADF family proteins (Tholl et al, 2011). In addition, it has been noted that the activities of ADFs from various organs or plant species may differ slightly.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, no similar study has been reported in plants. Previous studies have shown that the biochemical activities of ADF isovariants can vary greatly (Tholl et al, 2011), emphasizing the importance of characterizing the biochemical activity of each isovariant carefully before assessing its function in vivo. For example, a previous study showed that lily (Lilium longiflorum) pollen ADF1 binds to F-actin better and has less depolymerizing activity than the vegetative maize (Zea mays) ADF3 ).…”
Section: Introductionmentioning
confidence: 99%
“…V-ATPase B subunits in Arabidopsis show actin binding, bundling, and stabilizing activities in vitro (24), despite an absence of reports on actin-bundling functions for members of this protein family in animals or yeast. Interestingly, Arabidopsis actin depolymerization factor 9 (ADF9) facilitates F-actin bundling in vitro (25), and SB401, a pollen-specific protein from Solanum berthaultii, also exhibits bundling activity (26). These results imply that plants may have mechanisms for the formation and regulation of higher order actin structures that are distinct from the mechanisms in animals.…”
mentioning
confidence: 74%
“…Indeed, only a small number of actin-bundling proteins have been identified in plants to date. These proteins include the conserved ABP family proteins, such as villin, fimbrin, LIM, and formin (4 -5, 8 -13, 16, 18), plant-specific ABPs, such as SCAB1 (22), and plant ABPs with bundling activities, such as the V-ATPase B subunit and ADF9 (24,25). However, the mechanism of higher order actin bundle formation remains unknown.…”
Section: Discussionmentioning
confidence: 99%